ANALISIS KUANTITAS AIR TANAH BEBAS MENGGUNAKAN PENDEKATAN DEBIT DINAMIS DI KECAMATAN TEMON, KABUPATEN KULON PROGO, YOGYAKARTA - Novianto, Arif; Sejati, Sadewa Purba (J SIG (Jurnal Sains Informasi Geografi), 2023)
Groundwater in Temon District, Kulon Progo Regency, has the potential to experience pressure due to massive land use change. The quantity of groundwater in Temon District needs to be identified to determine the existing groundwater condition. The study was conducted to determine the amount of groundwater in the Temon District. The data used in the study include groundwater depth data, elevation data, groundwater level data, and data related to aquifer characteristics. Primary data were collected through field surveys. Secondary data are extracted through literature studies. Data analysis was carried out using the Darcy method. The results showed that the dynamic quantity of groundwater amounted to 4,996.3 m3/day. Factors affecting the active portion of groundwater include aquifer characteristics, groundwater depth, and groundwater hydraulic slope. Based on a comparison with the results of previous studies, it is known that there was a decrease in groundwater for five years (2016 to 2021) of 8,089,710 m3/year. The average reduction per year is 1,617,942 m3/year. Factors that influence the decrease in groundwater quantity are changes in land use and massive groundwater use.